The analysis and design of deep-sea lighting field based on spectral transfer function - Quan, Xiangqian; Wei, Yucong; Liu, Kaibin; Li, Bo (Frontiers in Marine Science, 2022)
Due to the attenuation of light in water, the deep-sea optical imaging system needs an active lighting system to provide the light source. However, because of the nonlinearity of light attenuation in spatial dimension and spectral dimension, the deep-sea lighting differs from terrestrial lighting. In order to quantitatively analyze and design deep-sea lighting system, we proposed a precise deep-sea lighting field simulation model and design method based on spectral transfer function. Firstly, with the analysis of deep-sea lighting-imaging process, the spectral transfer function in lighting field was analyzed and the deep-sea lighting model was built. Then, the platform used to study light attenuation was set up and the attenuation characteristics of light in water were derived. Moreover, the deep-sea lighting field simulation model was built with the computer program. Finally, the experiment platform for testing the underwater lighting field was set up in test pool. The experimental results show that the deep-sea lighting field computational model is accurate. In addition, the optimal deep-sea lighting system design was proposed. This study provides the theoretical basis and experimental data for the design of a deep-sea lighting system which has far-reaching significance for improving the efficiency of deep-sea scientific research.